Chatbot for Traditional Malay Museum - Misinem Misinem; Hafiz Muhammad Kurniawan; Fadly Fadly; Muhammad Raihan Hanif (CV Media Inti Teknologi, 2025)
Background of study: Museums play a key role in preserving cultural heritage and educating the public. In Malaysia and Indonesia, over 150 traditional Malay museums attract millions of visitors annually. Between 2015 and 2017, the Department of Museum Malaysia recorded 9.1 million visitors, while Indonesia reported over 12 million. Managing visitor inquiries manually poses challenges for museum staff, highlighting the need for an automated information system.Aims: This study aims to develop a chatbot for Muzium Adat to provide instant, accurate, and accessible information to visitors, thereby reducing dependence on staff and enhancing the visitor experience.Methods: A museum information chatbot was developed to answer frequently asked questions related to Muzium Adat. The system was tested through questionnaires distributed to 15 respondents to assess usability, accuracy, and satisfaction.Result: Findings showed that the chatbot achieved an 83.6% satisfaction and accuracy rate, indicating effective real-time interaction and reliable responses.Conclusion: The Muzium Adat chatbot improves communication efficiency, saves time, and enhances visitor engagement. It demonstrates the potential of chatbot technology to support museum operations and promote cultural heritage in Malaysia and Indonesia.